(untitled) (GEOmedia, 2008)
The international geocommunity meets at Intergeo 2008 The 2008 edition of Intergeo, a geodesy and land management fair, was held in Bremen. More than 15.000 visitors passed through the three days fair, which featured several international companies and was highlighted by an important congress ession.